UTILIZATION OF MIGRANT WORKERS' REVENUES (REMITTANCE) FOR THE FAMILY ECONOMY - Habib, Muhammad Alhada Fuadilah; Anggraeni, Unsiyah; Nisa, Kanita Khoirun (Universitas Wijaya Kusuma Surabaya, 2021)
It is undeniable that the high unemployment caused by the imbalance between the number of employment and labor force encourages people to work as migrant workers. In 2016, East Java province was the third largest supplier of migrants in Indonesia and Tulungagung contributed 4,962 inhabitants. This phenomenon is interesting to analyze the utilization of income sent to families in their country. The data used was a primary data conducted by the survey method to 100 respondents. The selection of research sites (sub-district and village) was carried out by simple random sampling while the respondent selection was done by systematic random sampling technique. To deepen the findings of data conducted indepth interviews with 10 informants.Â Moreover, the results revealed that remittances were used by the family for daily consumption needs, investment in childrenâ€™s education, religious ceremonies, home reparation, production activities and others. The authors recommend establishing a